Kewajiban dan Hak Negara Dengan Warga Negara Dalam Demokrasi - Wandi Wandi; Restu permohonan Hasibuan; Sasmi Nelwati (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
The constitution in a country, including Indonesia, is the source and basis making rules that have main principles, such as the rights and obligations of citizens. Human rigidity is the basis inherent in men as a gift from God, while the rights and obligations of citizens are a gift from the state. These are both concepts included in the second amendment to the 1945 Constitution, and cannot even be separated from each other because the two have a close relationship. The rights and obligations of citizens are an essential requirement of state legal democracy and must be implemented by people or citizens. Therefore, conceptual and strategic steps are needed so that the life of the nation and state becomes correct and fair under the auspices of the laws of a democratic country.